Innovative Approaches by Non-State Actors in Household Waste Management in Mrican Village: Challenges and Opportunities - Saputra Boni; Fajri Hidayatul; Renaldi Irvan; Pegi Andre Lofika; Halawa Historis Soterman; Syolendra Dwi Finna (E3S Web of Conferences)
Household waste management in residential areas often faces significant challenges due to limited resources and minimal government intervention. This research explores innovative approaches applied by non-state actors in household waste management in Mrican Village, highlighting the challenges and opportunities arising from the Bendhung Lepen Community initiative. Using a qualitative research method with a case study approach, data was collected through in-depth interviews, participatory observation, and document analysis involving stakeholders such as community members, NGOs, and local government. This research emphasizes the urgency of implementing sustainable waste management practices in urban areas. The results of this study show that community-led waste management can be an innovation and a driver of neighborhood participation despite facing various obstacles, such as limited resources, community resistance, and weak collaboration with the local government. This study emphasizes the importance of the role of non-state actors in filling the void left by formal governance in waste management in residential areas. This research contributes significantly to the discussion on sustainable waste management in urban environments.